Herpes simplex laryngitis presenting as airway obstruction in a stroke patient. (2018) - Pradeep, Tejus; Bhoite, Rahul; Rooper, Lisa; Zhang, Jiaying
Abstract: We present the second confirmed report of HSV laryngitis in an adult stroke patient, resulting in complicated airway management issues. This rare presentation of laryngeal HSV in a stroke patient can interfere with speech, language, and swallowing functions and confounds the etiology of these issues, which can impact subsequent management.